INNOVATIVE ARCHITECTURE AND INDUSTRIALIZATION BUILDING SYSTEM IN THE CONSTRUCTION INDUSTRY OF PAKISTAN - Sania Rehman Memon; Furqan Javed Arain; Shahnila Ansari; Dr. Ruhal Pervez Memon; Samreen Shabbir (Spectrum of Engineering Sciences, 2025)
Industrialized Building System (IBS) construction has emerged as a sustainable method for enhancing productivity and mitigating the adverse environmental and social impacts associated with conventional construction practices. While a growing body of research has addressed management issues in prefabricated construction, a systematic summary and strategic framework for its optimization remain underdeveloped. This study aims to develop a framework for optimizing the use of industrialized building construction by integrating innovative architectural approaches and construction waste reduction strategies. Through a comprehensive review of best practices in prefabrication implementation, including adoption rates, construction methods, cost-effectiveness, and performance evaluation, this paper examines effective implementation strategies, industry prospects, and the enabling environment for technological application. Special focus is placed on design, production, transportation, and assembly processes. The findings offer an improved understanding of the critical factors influencing the success of IBS and provide practical guidance for enhancing future adoption, promoting sustainability, and advancing innovation within the construction industry.